Bioorganic polymer-based synthesis of cerium oxide nanoparticles and their cell viability assays. Issue 1 (January 2015) - Kargar, Hadi; Ghasemi, Faezeh; Darroudi, Majid
Abstract: A simple one-step, eco-friendly, and "green" approach for the preparation of monodispersed cerium oxide nanoparticles (CeO2 -NPs) are described. This process uses nontoxic and renewable degraded agarose as a natural matrix and mild reaction conditions. The agarose acted as a stabilizing and/or capping agent for the CeO2 -NPs. The CeO2 -NPs were successfully grown at different calcination temperatures within the agarose matrices, and their crystallite structures were characterized using various methods, including FESEM, PXRD, FTIR, TGA/DTA and UV–vis spectroscopy techniques. This process was found to be comparable to those obtained from conventional preparation methods that use hazardous materials proving to be an excellent alternative for the preparation of CeO2 -NPs, using bio-organic materials. In vitro cytotoxicity studies on L929 cells, a non-toxic effect in all concentration (up to 800 μg/ml) was illustrated and we believe that these samples will have viable applications in different fields in medicine.